1961
DOI: 10.1139/m61-063
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Inactivation of Infectivity and Hemagglutinin of Influenza Virus by Gamma Radiation

Abstract: Factors influencing the effects of gamma, irradiation on influenza A(PR8) virus suspensions have been investigated. In purified virus suspensions in physiological saline, the hemagglutinin was destroyed more rapidly than the infectivity. The addition of reagents such as histidine, sodium p-aminohippurate, ascorbic acid, or cystine to the saline suspension reversed this effect. It was also found that the effect of a given amount of gamma radiation on the infectivity and hemagglutinin was similar regardless of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1962
1962
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 3 publications
2
11
0
Order By: Relevance
“…Unsurprisingly, γ‐irradiation was also used for influenza virus vaccines. Polley and colleagues were one of the first to successfully prepare γ‐inactivated influenza virus vaccine 112 . Guinea pigs intraperitoneally immunized with γ‐inactivated A/PR8 (H1N1) induced high hemagglutination inhibition, and serum neutralization titres, conferring homologous protection.…”
Section: γ‐Ray Sterilization As a Superior Inactivation Methods For Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsurprisingly, γ‐irradiation was also used for influenza virus vaccines. Polley and colleagues were one of the first to successfully prepare γ‐inactivated influenza virus vaccine 112 . Guinea pigs intraperitoneally immunized with γ‐inactivated A/PR8 (H1N1) induced high hemagglutination inhibition, and serum neutralization titres, conferring homologous protection.…”
Section: γ‐Ray Sterilization As a Superior Inactivation Methods For Inmentioning
confidence: 99%
“…The primary target of γ‐ray irradiation is the microbial genome 125 . It causes strand breaks in the genetic material, rendering the pathogen replication deficient without causing significant denaturation of the structures and biological function of proteins 108 , 112 , 133 , 134 , 135 , 136 . For this reason, γ‐ray inactivation has been used in studies of protein chemistry of highly virulent pathogens, such as Ebola, Marburg and Lassa virus, generating a relatively low risk of infection for the experimenter 137 , 138 .…”
Section: γ‐Irradiated Pathogens Generate Th‐1‐skewed Immune Responsesmentioning
confidence: 99%
“…This was a close about 50y0 greater than that calculated to be required from the inactivation curves (9). After it was shown that each virus suspension was non-infective (lo), each was inoculated into a group of six guinea pigs, in amounts of 0.5 n~l per aniii~al by the ii~traperitoneal route.…”
Section: Introductionmentioning
confidence: 91%
“…Jordan and Icempe (2) found that viruses could be inactivated with retention of antigenicity by performing the gamma irradiation on samples packed in dry ice. Recently it was shown in this Laboratory that, by the addition of various protective agents t o purified suspensions of influenza virus, it was possible to destroy the infectivity yet t o retain most of the hemagglutinin content (9). I t is the purpose of this paper t o report the application of this work to the preparatioil of influenza and mumps virus vaccines and the results obtained with these vaccines on inoculation into small laboratory animals.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation